Tantangan Reintegrasi Sosial Residen Pasca Rehabilitasi di Lingkungan Masyarakat - Nabila Annisa; Nurjannah Nurjannah; Muhammad Syauki (Yayasan Literasi Sains Indonesia, 2026)
The rehabilitation process for individuals with drug dependence does not end when the formal program is completed; rather, it continues into a more complex phase: social reintegration. Social reintegration refers to the process of returning former rehabilitation residents to a normal, productive, and dignified life within society. This study aims to explore the challenges, sources of support, and coping strategies of former residents during the post-rehabilitation phase. Using a qualitative approach with an exploratory design, data were collected through semi-structured interviews and participatory observations with former residents who had completed a rehabilitation program at least six months prior. Thematic analysis identified several key themes: social stigma, environmental support, access to employment, and individual resilience. The findings show that negative societal stigma remains a major barrier to reintegration, while support from family, the community, and rehabilitation institutions plays an essential role in sustaining recovery stability. Economic constraints and limited access to decent employment exacerbate vulnerability to relapse. Nevertheless, some former residents demonstrate psychological resilience and strong motivation to rebuild a better life. This study emphasizes that successful reintegration depends not only on the individual but also on socially supportive environments and inclusive policy systems. Therefore, a community-based approach, cross-sectoral synergy, and public policies oriented toward long-term recovery are needed to ensure that former residents can truly heal and become empowered members of society.